Social-comparison-based pedagogies for language learning through ludicization technology: Effects of pluralist learning and conformity-driven designs on performative and affective factors - Zhang, Qi (American Journal of Social Sciences and Humanities, 2025)
This study investigates how three social-comparison-based pedagogies: autonomous competitive framing (ACF), autonomous competitive framing with social reinforcement (ACF-SR), and pluralist learning (PL), influence performative and affective dimensions of educational-technology-supported language learning. Grounded in Social Comparison Theory, these pedagogies are compatible with ludicization settings implemented by Habitica as the educational technology. The empirical pedagogical interventions elicit the comparative analyses of the performative factor (Post-intervention language learning outcomes) and affective factors (openness, agency, and engagement). The one-way ANCOVA controlling for pretest performance demonstrates that learners in the PL group achieve the highest language performance, followed by those in the ACF, and finally by those in the ACF-SR groups. The K-means clustering analysis produces emergent affective profiles significantly aligning with the predefined pedagogical grouping. The Kruskal-Wallis analysis based on the three distinct affective configurations indicates that learners in the PL achieve higher openness, agency, and engagement than those in ACF, which features low agency, and ACF-SR, which features the lowest levels of all affective factors. Theoretically, these findings address how visibility, authority, and conformity pressures reshape social comparisons under ludicized learning conditions. Regarding pedagogical discussions, this study reflects on how social comparison can be reconstructed into performative and affective empowerment through ludicization as a holistic social-psychological process based on educational technology. In conclusion, this study reflects the facilitation of diversity-featuring pluralist learning in educational-technology-mediated language learning enhancement and the debilitation of conformity-driven designs in learning initiatives without performative or affective empowerment.